DINAMIKA HUBUNGAN MUHAMMADIYAH DAN PARTAI POLITIK DI INDONESIA - Sholikin, Ahmad (Jurnal Polinter : Kajian Politik dan Hubungan Internasional; Vol 5 No 2 (2020)DO - 10.52447/polinter.v5i2.4050, 2020)
Muhammadiyah's contact with political parties in actualizing their ideas  and ideals will be discussed in this chapter. Muhammadiyah's involvement with  political parties from the pre-independence era until now is divided into 4  patterns of relations. If it is analogous to Muhammadiyah's relationship with a  Political Party like a marriage, there will be four "Marriage" models between  Muhammadiyah and the Political Party. First is "Official Marriage" with  Muhammadiyah being a special member of Masyumi, second is "Siri Marriage"  when Muhammadiyah becomes the initiator of the establishment of Parmusi in  Tanwir Ponorogo. Third "Mut'ah Marriage (Contract)" when some  Muhammadiyah administrators were involved in the establishment of the  National Mandate Party (PAN), to the point of disappointment that gave rise to  the Sun Nation Party (PMB). The fourth most recent model is not the "Marriage"  that takes place, but the "Divorce" of the Islamic purification and reform  organization with political parties as formulated in Tanwir Denpasar (2001).
Keywords: Muhammadiyah, Political Parties, Indonesia